Pengaruh Waktu Dan Suhu Reaksi Grafting Pada Proses Pembuatan Maleated Natural Rubber - Ade Putra; Yelmida Yelmida; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Natural rubber can be modified through the grafting process. of maleic anhydride (MAH). Maleic anhydrade has been grafted into natural rubber to make a compound called Maleated Natural Rubber (MNR). The aiming in this research is learning of the reaction time effect and the temperature of natural rubber grafting process. Furthermore,kinetics reaction of the grafting process has to be learned. Independent variables are 8 phr of MAH and 60 rpm rotor speed of internal mixer. Dependent variables are reaction temperature and reaction time, which are variated by 150oC, 155oC, 160oC, and 165 of reaction temperature, and 6, 8, 10, 12, 14 minutes of reaction time. The degree of grafting was determined by titrimetric method, meanwhile kinetics reaction is learned by assumption of pseudo - first order to get the value of the constant rate of reaction (k). The results showed the optimum temperature is 160oC  and reaction time is 12 minutes. Best conditions of the kinetics reaction has been obtained at reaction temperature 155o and 165oC, which produced constant rate of reaction is 0.004 min - 1, activation energy is 6107 cal / mo , hereby  the Arrhenius equation : k = 4,65 e-6071/RT  Keywords: grafting degree, maleic anhydric, maleated natural rubber, temperature, Arrhenius equation.